(untitled) (Zamonaviy dunyoda pedagogika va psixologiya, 2022)
This is one of the most touched up on topics in football, and it often involves clubs, players, coaches, and even football agents. Tapping up occurs when a football club attempts to persuade a player who is currently under contract with his current club to switch to them by offering him improved sporting and monetary incentives to do so. When looking at it in a larger sense, approaches in the tapping up process are made by player's representatives pushing for a transfer to another club, coaches or other club players openly proclaiming their adoration for a specific player when speaking to the media. This article aims to address the challenges that clubs and players face while dealing with contractual relations at a club level, same time issues that are directly connected with keeping contractual stability in their businesses in football sector.